Modified versus three-level technique of retroperitoneal laparoscopic adrenalectomy for all patients with adrenal lesions ≤ 6cm: a retrospective, case-controlled study - Hu, Minxiong; Wu, Yangbiao; Xu, Xiao; Cai, Wenchao; Lin, Jiangui; Cai, Wanghai; Pan, Honghong; Yang, Zesong; Ye, Liefu; Wu, Jinfeng (Frontiers in Endocrinology, 2024)
The modified three-level technique for retroperitoneal laparoscopic adrenalectomy (RLA) has proven beneficial in the treatment of adrenal lesions in patients with BMI≥25 Kg/m 2 . This paper aims to summarize our institution's seven-year experience using this technique for all patients with Adrenal Lesions ≤ 6cm.: Between January 2016 and December 2022. The patients underwent laparoscopic adrenal surgery were categorized into Zhang's technique (ZT) (Three-level Technique) group and modified technique (MT) group. The fundamental characteristics and perioperative data were analyzed, with statistical significance set at p<0.05. Results: In total, 731 patients were stratified into two groups: ZT (n=448) and MT (n=283). Statistically significant distinctions were not detected between the two groups regarding sex, BMI, tumor location, tumor size, tumor type, or American Society of Anesthesiologists (ASA) score (p>0.05). The MT group demonstratedsuperior outcomes compared to the ZT group in terms of operative time, estimated blood loss, drainage volume, diet recovery time, complication rates, and postoperative hospitalization duration (p<0.05). 17 (4.34%) in the ZT group required unplanned adrenalectomy, while there was none in MT group (P<0.05).MT retroperitoneal laparoscopic adrenalectomy has demonstrated its benefits in the treatment of adrenal lesions across all patients with adrenal lesions ≤ 6cm, serving as a valuable point of reference for the surgical management of adrenal diseases.